(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This article analyzes the process of formation and territorial division of residential buildings in the historical centers of Samarkand. Samarkand is a city with a long history, whose residential architecture and territorial structure have developed under cultural, social, and economic influences. The article highlights the planning of city centers in ancient and medieval periods, the significance of local traditions and urbanization processes, as well as modern urban planning experiences. Additionally, it examines the socio-economic aspects of residential areas and the challenges of preserving historical heritage.